2015
DOI: 10.1016/j.conbuildmat.2015.08.127
|View full text |Cite
|
Sign up to set email alerts
|

Glass encapsulated minerals for self-healing in cement based composites

Abstract: This study presents the encapsulation of mineral compounds as healing materials for cement-based composites. Three liquid (sodium silicate, colloidal silica and tetraethyl orthosilicate) and one powdered (magnesium oxide) minerals were encapsulated in thin walled soda glass capsules. Load regain was obtained for samples healed under three different curing regimes; ambient conditions, high humidity exposure or immersed in water. Water immersion resulted in crack area closure that ranged from 85% to 100% for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(81 citation statements)
references
References 27 publications
0
74
1
2
Order By: Relevance
“…When in contact with the calcium hydroxide present in concrete, sodium silicate interacts chemically to produce crystalline and amorphous products that can promote healing. Recent results showed that liquid sodium silicate considerably improved the self-healing efficiency in cracked mortar specimens [27]. Recent attempts to produce microcapsules for cement-based materials include the use of polymeric microcapsules for encapsulating sodium silicate [28,29].…”
Section: +mentioning
confidence: 99%
“…When in contact with the calcium hydroxide present in concrete, sodium silicate interacts chemically to produce crystalline and amorphous products that can promote healing. Recent results showed that liquid sodium silicate considerably improved the self-healing efficiency in cracked mortar specimens [27]. Recent attempts to produce microcapsules for cement-based materials include the use of polymeric microcapsules for encapsulating sodium silicate [28,29].…”
Section: +mentioning
confidence: 99%
“…The benefit of using polymer as shell materials is it has good sealing function to the healing agent, which is believed as a crucial factor for most of healing agent that would lose effect when it encounters with high alkaline solution. Inorganic microcapsule is another category of microcapsules that employing inorganic materials such as silica particles [38], glass capsules [39], expanded clay [4] as shell materials. Due to the similar properties of materials, the advantage of inorganic microcapsules is the relatively good bonding strength with cementitious matrix, which is believed to have a influence on the trigger efficiency of microcapsules.…”
Section: Microencapsulationmentioning
confidence: 99%
“…В данном случае контактный слой включает два независимых компонента -контактную зону заполнителя, прилегающую к цемент-ному камню, и контактную зону цементного камня около поверхности заполнителя. Поиск путей решения данной проблемы является акту-альным направлением исследований как в России, так и за рубежом [12][13][14][15][16].…”
Section: легкие бетоныunclassified